Communication Satisfaction of SUC’s Faculty Members - Butac, Susan (International Journal of Arts, Sciences and Education, 2021)
Abstract The study described the communication satisfaction of the permanent faculty members of State Universities and Colleges at the National Capital Region in terms of Interpersonal Communication, Group Communication, and Organizational Communication. It intended to provide answers to the question, “What is the level of communication satisfaction of SUC’s faculty members in terms of Interpersonal communication context; Group communication context; and Organizational communication context?” The study utilized the Quantitative design of research. The descriptive method particularly the Descriptive survey as the most appropriate one was employed since the study focused on the quantitative data which are the levels of Communication Satisfaction of 377 regular faculty members of SUCs at the NCR in terms of Interpersonal Communication, Group Communication, and Organizational Communication. The needed Quantitative data were obtained using the modified communication satisfaction survey questionnaire of Downs and Hazen (1977). The results of the study indicate that the level of communication satisfaction of SUC’s faculty members was Significantly Satisfied in terms of the Communication dimensions. The Communication Satisfaction level of SUC’s faculty members at the NCR is Satisfied. Their feeling of being contented with their existing communication system in terms of Interpersonal Communication, Group Communication and Organizational Communication is proven very significant in doing their job. It can be inferred also that Communication Satisfaction promotes Job Satisfaction and productivity in some areas. Communication satisfaction is a variable option in determining these aspects. Keywords: communication satisfaction, interpersonal communication, group communication, organizational communication